Diet adequacy and food cost of food-secure and insecure households evidence from the 2018 ENNS - Javier, Charina A. (Philippine Journal of Science, 2024)
Access to a nutritious diet is a challenge that often strains many households with limited resources, thus making food choices that are short of recommended intakes. The study compared the one-day food consumption of households in the Philippines in terms of cost and nutritional adequacy by food security status. It also used the food threshold as a reference value for meeting the minimum cost required to meet basic food needs and satisfy energy and nutrient requirements. Secondary data from the 2018 Expanded National Nutrition Survey done by the Department of Science and Technology–Food and Nutrition Research Institute was used in the analysis. Food-insecure households have significantly higher intakes of energy-giving foods such as rice and other cereals and significantly lower intakes of body-building food such as fish, meat, and poultry than food-secure households. Less than half (45.0%) of the households have food costs equal to or higher than the food threshold. Households whose food cost was equal to or higher than the food threshold were 2.86 times more likely to meet their energy adequacy than those who had lower than threshold food costs. Similarly, households who met the food threshold were 4.61 times more likely to meet their protein, 2.11 times more likely to meet their vitamin A, and 1.87 times more likely to meet their iron adequacies, holding other variables constant. The study highlights the importance of economic access to food, especially among food-insecure households. This could be through making food more affordable and reducing physical barriers to food to be more accessible to poor communities or providing livelihood opportunities to increase their means to acquire food.